The effect of role clarity on the relationship between transformational, transactional and laissez-faire leadership styles and commitment to service quality - Pahi, Munwar Hussain (2017)
The effectiveness of leadership style initiatives resulting in sustainable competitive advantage and enhanced commitment to service quality has been a major subject of interest for business and academia alike. past research frequently cites the importance of leadership style (transformational, transactional, and laissez-faire) and commitment to service quality, but only little research has been done to evaluate the linkages between leadership styles and commitment to service quality. Drawing upon cognitive dissonance theory and path goals theory, this study examined the relationship between the transformational, transactional and laissez-faire leadership style and commitment to service quality. This study also examine the moderating effect of role clarity on the relationships between three leadership styles (transformational, transactional, and laissez-faire leadership styles) and commitment to service qualityin public hospitals of Sindh Pakistan. A quantitative research design was adopted to collect data, test hypotheses, and answer the research questions. A cross-sectional survey method was used to conduct this study.Using the multi-stage cluster sampling technique, a total of 315 survey responses were collected from the medical officers working the 43 public hospitals in Sindh, Pakistan. The data was analyzed using SmartPLS 2.0 software. The findings of the study revealed supports for the hypothesized three direct influences of transformational, transactional, and laissez-faire leadership style on the commitment to service quality. While role clarity was found to moderate the relationships of two leadership styles, namely transformational leadership and laissez-faire leadership with commitment to service quality, significant moderating effect was not evident for the association between transactional leadership and commitment to service quality. The present study had also discussed the theoretical and practical implications.